Aids behind closed doors - Chitty, Andrew; Barmer, Chris (London : Horizon Aids [production company] ; Bristol : BBC Education and Training [distributor])
Discussion about the AIDS economic in the 3rd world. Discussing the viruses, vaccines and preventions AIDS disease
Film editor, Brian Trenerry ; series editor, John Lynch
Keywords: AIDS (Disease) -- Prevention; AIDS vaccines; HIV (Viruses)